2009
DOI: 10.22358/jafs/66425/2009
|View full text |Cite
|
Sign up to set email alerts
|

Performance, intestinal microflora, and blood constituents in finishing turkeys fed diets supplemented with dietary mannan oligosaccharide and live yeast

Abstract: This study was designed to evaluate the effects of dietary mannan oligosaccharide (MOS) and Saccharomyces cerevisiae (SC) in finishing turkeys' diets on performance, intestinal microflora, duodenal viscosity and pH, and blood constituents. A total of seventy-two, Big6, 10-week-old, male poults were divided into three dietary treatments and eight replicate pens per treatment. Treatments including the following: 1. basal diet (control -C, no additive), 2. addition of MOS 1 g per kg basal diet, and 3. SC 1 g per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
6
4
0
Order By: Relevance
“…There were no significant (P≥0.05) differences across the different dietary treatments in serum levels of total protein, globulin and triglycerides. These results are in line with the results obtained by [27] who reported that inclusion of yeast into diets of turkey toms doesn't affect serum levels of total protein, globulin and triglycerides. Reference [28] also, found serum levels of protein and triglycerides were unaffected by dietary S cerevisiae.…”
Section: Resultssupporting
confidence: 92%
“…There were no significant (P≥0.05) differences across the different dietary treatments in serum levels of total protein, globulin and triglycerides. These results are in line with the results obtained by [27] who reported that inclusion of yeast into diets of turkey toms doesn't affect serum levels of total protein, globulin and triglycerides. Reference [28] also, found serum levels of protein and triglycerides were unaffected by dietary S cerevisiae.…”
Section: Resultssupporting
confidence: 92%
“…However, supplemental LY failed to induce modifications of growth performance in broilers during normal period or stress period. This result was similar to the previous studies (Heugten et al 2003;Konca et al 2009). Contradictorily, it was also reported that LY addition was associated with the promotion of growth in broilers (Haldar et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Several study reported that either MOS from yeast cell walls (Kim et al, 2011) or MOS from palm cernel (Fernandez et al, 2002) reduced the population of E.coli significantly compared with control feed. In agreement with our results, in a comparative study, Chee et al (2010) and Biggs et al (2007) reported that supplementation of MOS in diet did not reduce the population of E.coli in the intestine of broilers, while Konca et al (2009) reported that supplementation of MOS in diet did not reduce the population of E.coli in the intestine of turkey.…”
Section: Effect Of Dietary Mos On Intestinal Microbial Populationssupporting
confidence: 92%
“…(Sirvydis et al, 2006). On the other hand, several study reported that commercial MOS did not affect neither the blood constituents of turkey (Konca et al, 2009) nor immune response of broilers (Kim et al, 2011). MOS had been reported to have immunomodulation effect.…”
Section: The Effect Of Dietary Mos Administration On Blood Profilementioning
confidence: 95%